2017
DOI: 10.1111/jgh.13646
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding ribonucleic acid zinc finger antisense 1 promotes the progression of colonic cancer by modulating ZEB1 expression

Abstract: Long non-coding RNA ZFAS1 may function as an oncogene by modulating ZEB1 to induce EMT. Manipulation of ZFAS1 level may be a novel approach to suppress colonic cancer progression. In addition, ZFAS1 in plasma has the potential to be a diagnostic biomarker of colonic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…Some transcriptional factors could bind to the promoter region of E-Cadherin to suppress its expression, and further trigger the EMT conversion and metastasis of tumor cells, including SNAIL, SLUG, ZEB1 and ZEB2 [33, 34]. Among them, ZEB1 (characterized by the presence of 2 zinc finger clusters) is a well investigated transcriptional factor to act as a driver of EMT and cancer progression toward metastasis and invasion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some transcriptional factors could bind to the promoter region of E-Cadherin to suppress its expression, and further trigger the EMT conversion and metastasis of tumor cells, including SNAIL, SLUG, ZEB1 and ZEB2 [33, 34]. Among them, ZEB1 (characterized by the presence of 2 zinc finger clusters) is a well investigated transcriptional factor to act as a driver of EMT and cancer progression toward metastasis and invasion [35].…”
Section: Discussionmentioning
confidence: 99%
“…Then they found ZFAS1 inhibition could markedly suppress CRC cell lines proliferation and invasion both in cell lines and mouse models of proliferation and metastasis. Another study by Fang et al [33] found ZFAS1 was up-regulated in colonic cancer tissues compared with adjacent mucosa, and its expression level was significantly correlated with TNM stage, vascular invasion, and lymph node metastasis. In addition, they found knockdown of ZFAS1 impeded proliferation, invasion, and promoted apoptosis of colonic cancer cell lines.…”
Section: Zfas1 In Various Cancersmentioning
confidence: 99%
“…Nie et al also revealed that lncRNA ZFAS1 could mediate the carcinogenic effects in GC partially through silencing the KLF2 and NKD2 expression by binding with PRC2 and LSD1 [19]. Epithelial-Mesenchymal Transition (EMT) was mentioned in one study that the author suggested that lncRNA ZFAS1 induce EMT by elevating ZEB1 expression [12].…”
Section: Publication Biasmentioning
confidence: 99%
“…However, there were opposite findings that elevated lncRNA ZFAS1 occurred in gastric cancer, hepatocellular carcinoma and glioma. The function of lncRNA ZFAS1 in cancer cells might be cell type-dependent [12][13][14][15][16][17][18][19][20]. Therefore, we need a systematical and comprehensive meta-analysis to explore whether overexpression of ZFAS1 in tumor are related to worse outcome.…”
Section: Oncotarget 2 Wwwimpactjournalscom/oncotargetmentioning
confidence: 99%
See 1 more Smart Citation